UPAYA UNITED NATIONS (UN) WOMEN DALAM MEMPROMOSIKAN HAK ASASI MANUSIA (HAM) PEREMPUAN INDONESIA - Yolanda, Dina; Iskandar, Irwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The rights to freedom and equality are rights that every human being should have. It is a basic right that is inherent in a human being. Women are the victims of this inequality. In Indonesia, women are perceived as reproductive and domestic workers. This is inseparable from the patriarchal culture, which considers women to be at home, giving birth, cooking and serving men at home. UN Women is an organisation dedicated to gender equality that supports every UN member to achieve equal empowerment of women. Looking at the situation in Indonesia, UN Women is endeavouring to promote human rights for Indonesian women. This research uses Qualitative research methods. Qualitative research, namely analysing data in this study using qualitative analysis, namely research that describes content but is not based on statistical accuracy. The data that has been collected, processed and analysed according to the problems studied. Using data collection techniques sourced from journals, books, official documents, reports, and official websites. This research uses the perspective of pluralism with the level of analysis, as well as the theory of international organisations. UN Women has been working to provide support to the Indonesian government, civil society organisations, academia, media, public, private sectors and others. In ending violence against women in Indonesia, UN Women established the HeForShe Campaign and Adopted RAN P3AKS). On economic empowerment UN Women created Cash For Work and WeEmpowerAsia. And in the women's peace sector, there is the Peace Village Programme. Keywords: Human rights, Equality, UN Women, Empowerment